2018
DOI: 10.1021/acs.joc.8b01094
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) Coordination Polymer as a Precatalyst for Selective Hydroboration of Aldehydes, Ketones, and Imines

Abstract: Highly effective hydroboration precatalyst is developed based on a cobalt(II)-terpyridine coordination polymer (CP). The hydroboration of ketones, aldehydes, and imines with pinacolborane (HBpin) has been achieved using the recyclable CP catalyst in the presence of an air-stable activator. A wide range of substrates containing polar C═O or C═N bonds have been hydroborated selectively in excellent yields under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 50 publications
5
70
1
Order By: Relevance
“…Both the C ‐ and N ‐phenyl ring of the imine moiety bearing diverse substituents resulted the desired products. Various substituents on C ‐phenyl ring afforded the secondary amines ( 3 a – e ) in excellent yields of 85–92 % and these results are significantly better than those observed for Co II ‐CP, Ru II , and (MeCp) 3 La systems which require higher temperature (60–70 °C) and longer reaction duration. Presence of substituents at the N ‐phenyl ring demands longer reaction span than their analogues C ‐phenyl substituted imines ( 3 h – j vs. 3 a – e ).…”
Section: Methodsmentioning
confidence: 86%
“…Both the C ‐ and N ‐phenyl ring of the imine moiety bearing diverse substituents resulted the desired products. Various substituents on C ‐phenyl ring afforded the secondary amines ( 3 a – e ) in excellent yields of 85–92 % and these results are significantly better than those observed for Co II ‐CP, Ru II , and (MeCp) 3 La systems which require higher temperature (60–70 °C) and longer reaction duration. Presence of substituents at the N ‐phenyl ring demands longer reaction span than their analogues C ‐phenyl substituted imines ( 3 h – j vs. 3 a – e ).…”
Section: Methodsmentioning
confidence: 86%
“…Therein, the product amino organoborons are a class of versatile building blocks in organic synthesis and potent protease inhibitors in medicinal chemistry . However, among these multiple C─N materials, imines are extensively used in the synthesis of agrochemicals, polymers, dyestuffs, pigments, and textiles and act as protectants against damage from γ‐radition and is also a good reagent for the synthesis of N ‐borylamines. What is more, imines are readily available from the condensation of carbonyl compounds and primary amines and are, thus, the precursors of choice for the synthesis of unsymmetrically substituted secondary amines .…”
Section: Introductionmentioning
confidence: 99%
“…What is more, imines are readily available from the condensation of carbonyl compounds and primary amines and are, thus, the precursors of choice for the synthesis of unsymmetrically substituted secondary amines. [35][36][37] Although the hydroboration of imines had been reported more and more, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]28,[38][39][40] it is worth noting that hydroboration of C N bonds with organoboranes or borohydrides is a workhorse reaction for the mild reduction of imines into amines. Especially, the use of deactivated hydroboranes, such as catecholborane (HBCat, Cat = catechol) and pinacolboane (HBPin, Pin = pinacol), requires catalysis due to the significantly decreased Lewis acidity of the boron center.…”
Section: Introductionmentioning
confidence: 99%
“…reported that hydroboration of aldehydes and ketones with powdered NaOH as catalyst and HBpin. Wu and coworkers reported the use of a cobalt(II) coordination polymer and KO t Bu as the activator to catalyze the hydroboration of aldehydes and ketones . We previously developed an effective method for the selective hydroboration of aldehyde over ketones with sodium hydride (NaH) .…”
Section: Introductionmentioning
confidence: 99%
“…Wu and coworkers reported the use of a cobalt(II) coordination polymer and KO t Bu as the activator to catalyze the hydroboration of aldehydes and ketones. 8 We previously developed an effective method for the selective hydroboration of aldehyde over ketones with sodium hydride (NaH). 9 Stachowiak et al 10 reported the solvent-and catalyst-free hydroboration of aldehydes, but this method was not feasible to other carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%